Competing in capabilities : the globalization process - Sutton, John, 1948- (Oxford : Oxford University Press, 2013)
This text offers a new perspective of globalization. The author moves away from the established 'For or Against' debates and shows what the globalization process looks like from Chinese Indian, and African perspectives.
Series from CIP print record.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Nov. 13, 2012).
Keywords: Economic development -- Developing countries; Globalization -- Economic aspects; International economic relations; International business enterprises -- Developing countries